2011
DOI: 10.1128/mcb.00943-10
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Drosophila Integrator Proteins Is Essential for Efficient U7 snRNA and Spliceosomal snRNA 3′-End Formation

Abstract: Proper gene expression relies on a class of ubiquitously expressed, uridine-rich small nuclear RNAs (snRNAs) transcribed by RNA polymerase II (RNAPII). Vertebrate snRNAs are transcribed from a unique promoter, which is required for proper 3-end formation, and cleavage of the nascent transcript involves the activity of a poorly understood set of proteins called the Integrator complex. To examine 3-end formation in Drosophila melanogaster, we developed a cell-based reporter that monitors aberrant 3-end formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(134 citation statements)
references
References 56 publications
16
118
0
Order By: Relevance
“…We therefore constructed a reporter gene that relies on a promoter derived from the Drosophila U7 snRNA gene. snRNA genes associate with a distinct set of transcriptional factors, and primary transcripts generated from these genes (pre-snRNAs) are cleaved at the 3 ′ end by a distinct machinery termed Integrator that shares no common components with the two types of 3 ′ -end processing machineries operating on premRNAs (Baillat et al 2005;Egloff et al 2008;Ezzeddine et al 2011).…”
Section: Components Of the Hcc Essential Formentioning
confidence: 99%
“…We therefore constructed a reporter gene that relies on a promoter derived from the Drosophila U7 snRNA gene. snRNA genes associate with a distinct set of transcriptional factors, and primary transcripts generated from these genes (pre-snRNAs) are cleaved at the 3 ′ end by a distinct machinery termed Integrator that shares no common components with the two types of 3 ′ -end processing machineries operating on premRNAs (Baillat et al 2005;Egloff et al 2008;Ezzeddine et al 2011).…”
Section: Components Of the Hcc Essential Formentioning
confidence: 99%
“…Perhaps the longer 3 ′ box evolved for snRNA processing because it is the only RNA sequence element required for Integrator cleavage. Although the 3 ′ -terminal stem-loop of the Drosophila U7 snRNA is important for 3 ′ end processing with a GFP reporter attached (Ezzeddine et al 2011), others reported that such a stem-loop is not always essential for Integrator-dependent cleavage of snRNAs (Hernandez 1985;Yuo et al 1985). We likewise conclude that the HSUR4 terminal stem-loop is not essential for snRNA 3 ′ end processing, since removing the entire HSUR4 sequence does not affect miR-HSUR4 production, which requires 5 ′ cleavage by Integrator (Cazalla et al 2011).…”
Section: An Unusual Integrator Cleavage In Hvs Mirna Biogenesismentioning
confidence: 99%
“…Although the 39 box is highly tolerant of mutation (Hernandez 1985;Ach and Weiner 1987;Ezzeddine et al 2011), it is likely to be a binding site in the RNA for the machinery that governs snRNA 39-end formation. Studies have also shown that substituting either human or Drosophila snRNA promoters with mRNA promoters results in total loss of snRNA 39-end formation (de Vegvar et al 1986;Hernandez and Weiner 1986;Ezzeddine et al 2011). In addition, the 39-end formation of viral-encoded snRNAlike transcripts found in Herpesvirus saimiri also exhibits a dependency on an snRNA promoter (Cazalla et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…New insight to these snRNA processing events has come from the biochemical purification of the Integrator complex and establishment of its functional requirement in snRNA 39-end formation (Baillat et al 2005;Ezzeddine et al 2011). Integrator subunit 9 (IntS9) and IntS11 (Albrecht and Wagner 2012) are homologous to CPSF100 and CPSF73, which are components of the cleavage factor for mRNA 39-end formation (Mandel et al 2006;Sullivan et al 2009).…”
Section: Introductionmentioning
confidence: 99%